Psychological-Related Challenges in Speaking: Experience of Vocational Students - Sulindra, Eric; Hartani, Tuti; Cendra, Anastasia Nelladia (Journal of Education Reseach and Evaluation, 2023)
Speaking is still often considered one of the most daunting skills for English language learners. For Asian learners, such as Indonesian, it is quite common for them to experience psychological-related challenges whenever they are presented with speaking tasks. The aims of this research aims to analyze the psychological challenges of students in vocational education at the higher education level.This study uses a qualitative descriptive approach. Respondents in this study are 36 students. The data in this study were sourced from the experiences of the respondents which were recorded in their guided reflection and semi-structured interviews.The data from the reflection results were analyzed using three coding steps: open coding, axial coding, and selective coding. This study found that most participants reported negative feelings around speaking tasks, such as being nervous, afraid (of making mistakes), fear of failure, insecure, tense, anxious, and doubtful, faster heartbeats and trembling which mostly stemmed from afraid to failing to meet expectations, lack of preparation, and lack of adequate language competence. Suggestions for a better-speaking class are discussed.